Religious Violence in Indonesian Muslim Society - Burhanudin, Jajat (Studia Islamika, 2006)
Acts of violence in the name of religion have frequently in lndonesia in recent times, a country in zuhich most of its inhabitants are Muslim. Acts of violence are usually a result of efforts, for example, to eradicate sinful acts in society, wipe out shirk (idolatry), and defend God's name. Yet, this phenomenon of violence is indeed aery complex. It appears in a number of forms and involves a large variety of factors.DOI: 10.15408/sdi.v13i2.573